Prior antithymocyte globulin therapy and survival in post-transplant lymphoproliferative disorders. (3rd June 2021) - Kinch, Amelie; Baecklund, Eva; Molin, Daniel; Pauksens, Karlis; Sundström, Christer; Tufveson, Gunnar; Enblad, Gunilla
Abstract: Background: Treatment with antithymocyte globulin (ATG) is a well-recognized risk factor for the development of post-transplant lymphoproliferative disorders (PTLD) after solid organ transplantation, but it is unknown how its use affects overall survival after PTLD. Methods: A total of 114 patients with PTLD and available data on immunosuppressive regimen were included from a nation-wide case series of solid organ transplant recipients in Sweden. Prior use of ATG was correlated to clinical features, PTLD subtype, and survival. Results: A total of 47 (41%) patients had received ATG prior to the diagnosis of PTLD. The ATG-treated patients were more likely to be recipients of hearts or lungs, and less likely of kidneys ( p  < 0.01). They had experienced more acute rejections ( p  = 0.02). The PTLDs arose earlier, median 2.0 vs. 6.6 years post-transplant ( p  = 0.002) and were more often situated in the allograft (32% vs. 7%, p  < 0.001) in patients with prior ATG vs. no ATG treatment. The PTLDs in the ATG group were more often Epstein–Barr virus-positive (80% vs. 40%, p  < 0.001). There were more polymorphic PTLDs (17% vs. 1.5%, p  = 0.004) and less T-cell PTLDs (4% vs. 19%, p  = 0.02) in the ATG group than in the no ATG group. Diffuse large B-cell lymphoma was equally common in patients with and without prior ATG therapy, but the non-germinal center subtype was more frequent in the ATG group ( p  = 0.001). In an adjusted Cox proportional hazards regression model, prior ATG treatment and better performance status were associated with superior overall survival, whereas older age, T-cell subtype of PTLD, presence of B symptoms, and elevated lactate dehydrogenase were associated with inferior overall survival. Patients receiving ATG solely as rejection therapy had superior overall survival compared with those receiving ATG as induction therapy or both ( p  = 0.03). Conclusions: ATG therapy, especially rejection therapy, prior to PTLD development is an independent prognostic factor for superior overall survival after PTLD diagnosis.